Programação orientada a características em groovy - Guilherme Henrique de Assis (2016)
Software Product Lines (SPL) are increasingly present in the software market, because they are a software development paradigm that aims to reuse in order to reduce costs and gain agility. There are several ways to implement a SPL, and Feature Oriented Programming (FOP) is one technique that aims to improve modularity and flexibility of SPL. The basic idea of FOP is to decompose software into smaller pieces, called features, so they can be composed according to the needs of each customer. For the programming language Groovy, there are no tool and framework that supports the implementation of a SPL using FOP. Groovy is a progrraming language that has been growing in popularity in recent years. Given this scenario, this work proposes G4FOP, which is an extension of a framework called Feature House for the Groovy programming language. Feature House is a framework for software composition supported by a set of tools. In addition to present the extension to Feature House, this work demonstrates the use of this extension for composing features of a SPL sample. It is also presented how the structures of Groovy have been supported by G4FOP.